Educação popular e identidade: navegando com a associação artístico-cultural de Cabedelo - Cananéa, Fernando Antonio Abath Luna Cardoso (2015)
Does popular education strengthens peaople‟s identity? This is our main research. This chart was analysed at the NGO Associação Artistico-Cultural de Cabedelo - AACC - Paraíba, founded in 1985. I have collected meaningful speeches from people who work in pro their cultural identity and interviewed another meaningful group of people searching for different points of view towards this research. The conception applied was the one that show when people are incentivized to participate and practice popular education, this participation increases their sense of identity. Popular education practice as a demand expresses the human phenomena of people‟s identities growth. Solidifying the identity conquered, through the exercising of popular education practice. Through this perspective, it has been consolidated that POPULAR EDUCATION STRENGTENS PEOPLE‟S IDENTITY. People‟s participation strengthen the foundations of popular education process and therefore, analyzing some categories that constitute popular education as whole of identity. The process noticed at AACC since its foundation and mainly from 2003, landmark year when cultural events started to occur in town, with parades, presentations and debates around this theme and local culture, the facts show us that solidarity and commitment for the local culture and cultural practices are education exercises that strengthen the identity of the subjects envolved. This thesis POPULAR EDUCATION STRENGTENS PEOPLE‟S IDENTITY goals understanding popular education in a participative way as a strengthening point, in the period that comprehends January 2003 to December 2013; characterize these actions as popular education; Highlight popular education elements (speech, acknowledge and knowledge) amongst participating actions and emphasizing popular education identity fortifiers (culture, knowledge and criticizing). I used the dialectic approach and Research-Action methodology. At first, summarized the research environment, characterized the subjects and within these elements determined the hypothesis and problems to be researched. Also, chose the participation categories of popular education and identity as well bibliography search we took upon them. At second, interviewed and recorded people‟s opinions, shooting and filming, field journals, photographs, email files, documentations, experienced actions and informal records, highlighting the elements that contributed with the categories definition. Later, an analytic moment took place looking for a new summary where the previous movements point as a strengthening factor of the people‟s cultural identity through popular education of those in action. A theory effort to demonstrate the Paticipation/Practice and Identity as a full possibility net, from the dialectical exercising with its contradictions among human social relations. Therefore, it made possible to understand how the identity strengthening and growth occurs, ensuring this thesis.